Grassroots Movements for the Existence of Trees and Water in Gunungkidul: Between Tradition and Ecological Work - Ameylia Puspita Rosa Dyah Ayu Arintyas; Yogie Stefanus (Universitas Kadiri, 2026)
Gunungkidul is one of the regencies in the Special Region of Yogyakarta with the largest forest area compared to other regions. The uniqueness of this area is closely related to the strong traditions of local communities and their alignment with Yogyakarta’s cultural vision, Hamemayu Hayuning Bawana, which means maintaining the harmony and beauty of the world. Ecologically, Gunungkidul functions as a buffer zone for surrounding areas. However, the forests face serious threats due to logging for the furniture industry and land conversion into agricultural areas. If these practices continue without control, ecological damage such as flooding may occur, even though the region is widely known for its vulnerability to drought. In response, various grassroots movements based on local communities have emerged and developed. This study employs a netnographic (digital ethnography) approach through the analysis of online documents, particularly media reports and community digital publications, to trace representations, narratives, and meaning constructions of environmental movements in digital public spaces. The findings show that movements such as Resan Gunungkidul, Daksina Arga, and Sanggar Lumbung Kawruh not only promote tree planting but also reinterpret Hamemayu Hayuning Bawana and Traditional Ecological Knowledge as community-based ecological governance practices.